Hayat ve Hayat Dışı Sigorta Şirketlerinin Çok Değişkenli İstatistiksel Yöntemlerle Karşılaştırılması - (:unkn) unknown (My University, 2002)
0

The Aim of this paper is to decide on which factors are effective on insurance companies for the life branch and nonlife branch. To find out this,factor,discriminant and logistic regression analysis are used in this paper. Starting with thirty variables, some of the irrelevant variable are removed and factor analysis is applied to the remained thirteen variables.Using factor analysis on thirteen variables, two factors called profit factor and the reserve factor are obtained. Then, discriminant and logistic regression analysis are applied to new variables and results are compared. As a result, most critical factor for discriminating the life branch and nonlife branch insurance company is found to be the factor of reserves.